FN1 is a prognostic biomarker and correlated with immune infiltrates in gastric cancers - Wang, Han; Zhang, Junchang; Li, Huan; Yu, Hong; Chen, Songyao; Liu, Shuhao; Zhang, Changhua; He, Yulong (Frontiers in Oncology, 2022)
Fibronectin 1 (FN1) is a glycoprotein found throughout the extracellular matrix that has a role in the onset and progression of cancer. However, its immune relationship with gastric cancer is still unclear. FN1 was systematically reviewed by Gene Expression Profiling Interaction Analysis (GEPIA), Linked Omics, Tumor Immune Estimation Resource (TIMER), and Kaplan–Meier (KM) plotter analysis. The TIMER, GEPIA, TISIDB and cBioPortal databases investigated the association of FN1 with tumor immune infiltration and validated using immunohistochemistry. We discovered that tumor tissue expresses FN1 at a higher level than neighboring tissue, and those genes co-expressed with FN1 have a poor prognosis. At the same time, we discovered that increased FN1 expression was related with immunological infiltration, particularly macrophage infiltration. Using immunohistochemistry, we discovered that FN1 expression was tightly connected to M2 macrophages. It can be concluded that FN1 can affect the immunological microenvironment and is a prognostic marker in gastric cancer.